Awareness and knowledge of epilepsy among students in UiTM Puncak Alam campus - Azaili, Nor Amirah Syuhada (2016)
Epilepsy is a disease when there are hyper excitability of neuron and electrical storm forming in the brain. Epilepsy is most associated with stigma among the society and the patient often exposed to insult and humiliation due to lack of awareness and knowledge of epilepsy. This study is done in UiTM Puncak Alam to identify the level of awareness and knowledge of epilepsy among undergraduate students from seven different faculty. The questionnaire was divided into four part: demographic, awareness and previous experience of epilepsy, knowledge of epilepsy and knowledge of care during epileptic seizure. The questionnaires were distribute evenly between the seven faculty: faculty of pharmacy, faculty of health science, faculty of accountancy, faculty of business management, faculty of hotel and tourism management, faculty of art and design and faculty of education. The result was analyzed through the Statistical Package for the Social Sciences (SPSS) version 22.0 and Microsoft Excel. From the finding, majority of the students were malay (95.7 %) and female (81.6 %) were higher compared to male (18.4 %) students. From the result, about (93 .8 %) of students ever heard about epilepsy and only (7 .6 %) had attended a seminar or talk of epilepsy. on the whole, only (11.1 %) of students that have their family members with epilepsy. In the part of the knowledge of epilepsy, only (26.2 %) know the cause of epilepsy, (62.4 %) didn't think epilepsy is a transmittable disease and (34.6 %) did think epilepsy is heritable. In the last part, (94.3 % ) of students agree to keep away object during epileptic attack and only (7 .3 % ) did not agree to put something into the mouth of patient during seizure attack. In general, the level of awareness and knowledge among students in UiTM Puncak Alam was favorable.